Update of ČSN 73 4959 with Emphasis on Horizontal and Vertical Requirements on Boarding Edges of Platforms (Current Problems in Rail Vehicles, 2025)
This paper presents selected updates of the ČSN 73 4959 with emphasis on horizontal and vertical alignment requirements on boarding edges of railway platforms with a height of 550 mm above the top of the rail. It describes modifications of the nominal horizontal length between the boarding edge and the axis of adjacent track in the context of TSI INF requirements and structural gauging. Furthermore, it examines vertical requirements on the boarding edge, specifically considering the requirements of level access to the vehicle according to TSI PRM and discusses the urgency of coordinated action of the infrastructure manager and rolling stock producers to fully meet the level access requirements.
Keywords: platform; interoperability; horizontal alignment; vertical alignment; accessibility